2021
DOI: 10.28991/cej-2021-03091711
|View full text |Cite
|
Sign up to set email alerts
|

Curve Number Estimation for Ungauged Watershed in Semi-Arid Region

Abstract: The Benanain Watershed is located in East Nusa Tenggara with an area of 3,181 km2 and is divided into 29 sub-watersheds. The East Nusa Tenggara itself is an eastern region of Indonesia with a unique climate condition called semi-arid. The high rainfall intensity occurring in short duration results in large surface runoff and erosion. Floods and erosion in semi-arid areas due to sensitive soils to drought and heavy rainfall extremely. This paper presents the application of the Soil Conservation Services-Curve N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…Ethiopia is highly exposed to erosion during the heavy rain season between June and September. A study by Krisnayanti et al (2021) in Indonesia reported that a large volume of rainfall exceeds the soil infiltration capacity, resulting in excess erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia is highly exposed to erosion during the heavy rain season between June and September. A study by Krisnayanti et al (2021) in Indonesia reported that a large volume of rainfall exceeds the soil infiltration capacity, resulting in excess erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Typify the soil, land use, topography and heterogeneity of physical condition is important to be able to estimate runoff (Krisnayanti et al, 2021 ). Post-fire runoff events can mobilize pulses of MeHg and THg to streams, but (Patel et al, 2019 ) explain that Hg methylation does not run parallel to THg trends, and this is important given the biological implications of MeHg in the environment.…”
Section: Development and Resultsmentioning
confidence: 99%
“…In addition, Elshamy et al (2009) and Mengistu & Sorteberg (2012) assumed that a 1 °C increase in temperature would increase PET by 4% which leads to a decrease in SURQ. In addition, Krisnayanti et al (2021) correlate changes in runoff depth with rainfall.…”
Section: Climate Change Impact On Water Balance Componentsmentioning
confidence: 99%